2023
DOI: 10.3390/jcm12030984
|View full text |Cite
|
Sign up to set email alerts
|

Age and Sex Influence the Use of Modular Femoral Components in Total Hip Arthroplasty Performed for Primary Osteoarthritis

Abstract: The impact of age and sex on femoral component choices in modular total hip arthroplasty (THA) is still unknown. A regional arthroplasty registry was interrogated about a modular stem in THA performed for primary osteoarthritis, with the aims to assess the influence of age and sex on stems sizes and neck choices. A total of 6830 THAs were included: all THAs had a modular stem (with 15 necks and 27 combinations per side). Patients were stratified by age in decades and sex. Necks were grouped according to the ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Anthropometric variables such as height, weight, and foot length have been identified as potential indicators of the size of acetabular prostheses used in THA. Previous research has demonstrated a correlation between shoe size, height, weight, gender, and age with the size of knee and hip prostheses [ 12 , 13 ]. However, it is worth noting that no study to date has incorporated foot length as a variable in the prediction model.…”
Section: Discussionmentioning
confidence: 99%
“…Anthropometric variables such as height, weight, and foot length have been identified as potential indicators of the size of acetabular prostheses used in THA. Previous research has demonstrated a correlation between shoe size, height, weight, gender, and age with the size of knee and hip prostheses [ 12 , 13 ]. However, it is worth noting that no study to date has incorporated foot length as a variable in the prediction model.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the use of version-controlled neck and sex-based differences, Castagnini et al 19 reported that a version-controlled necks were prevalent in younger males and older females ( p < 0.001). Meanwhile, Gofton et al 9 reported no significant difference in neck selectivity as a sex-based function.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoarthritis (OA) is a chronic joint disorder linked to articular cartilage degeneration that affects numerous populations worldwide, especially the middle-aged and elderly people. [1][2][3] As a highly prevalent type of arthritis, $303 million people worldwide and 61.2 million patients in China had OA in 2017. 4,5 The risk factors of OA involve genetic susceptibility, obesity, severe joint damage, advanced age, and congenital deformities.…”
Section: Introductionmentioning
confidence: 99%